IMPLEMENTATION OF AN EFFICIENT VLAN NETWORK BASED ON IEEE 802.16 STANDARD USING OPNET SOFTWARE - Najm AL-ASADI, Mustafa Kareem; Najm AL-ASADI, Ali Kareem; AlBaghdadi, Meena; Ahmed, Ahmed Hussein (Journal of mechanics of continua and mathematical sciences, 2025)
Since Wi-Fi networks are dependent on the structure of the network and are unable to supply extra facilities, high latency in non-VLAN networks may be made more variable. Because of this, the isolation problem becomes more significant when it comes to adding problems to certain networks that include WLAN components that are acceptable. Rather than being a genuine relationship, virtual local area networks (VLANs) are a coherence that enables aggregation in a comparable transmission region. As a result, bundles are transmitted to ports that are on the same VLAN. In addition to reducing transmission speed, the layout of trademark VLANs increases the efficiency of faraway organizations. Execution of virtual local area networks (VLAN) significantly enhances the security of distant organizations by lowering the number of sites that get copies of data that are sent by switches. A separate virtual local area network (VLAN) is used to store fundamental data. This study compares remote organizations using virtual local area networks (VLAN) to other types of remote companies. Through the use of document transfer during major rush hour congestion and online reading applications, the proposed network is assessed for typical throughput and latency. Via the use of OPNET 14.5 modeler reconstruction, the simulation was carried out, and the findings indicate that the use of VLAN via remote organization resulted in a reduction in traffic and avoided delays in presentation. As a result of the positive correlation that exists between throughput and traffic, virtual local area networks (VLAN) diminish the throughput of an organization. In addition, we investigated the throughput in a remote VLAN network and discovered that the Wi-Fi traffic was 1500 for VLAN and 950 for non-VLAN based on seconds for bits-sec. This would be an improvement to the Wi-Fi model.